THE INFLUENCE OF ORGANIZATIONAL CLIMATE AND COMPENSATION ON THE WORK MOTIVATION OF DAILY JOURNALISTS AT THE ONLINE JOURNALISTS ASSOCIATION (IWO) MEDAN - Anna Putri Aulia; Risydah Fadilah; M Fadli Nugraha (Pena Cendekia Insani, 2026)
The study was to determine the effect of organizational climate and compensation on the work motivation of daily journalists at the Online Journalists Association (IWO) in Medan. This research used a quantitative method, with a population of 152 journalists and a sample of the entire population, namely 152 daily journalists at the Online Journalists Association (IWO). The researcher used a total sampling technique. The results showed a significant influence between organizational climate and work motivation, as seen from the calculated t-value of 21.242 and the t-table of 1.976. The significance value was 0.000, or less than the alpha value of 0.025. This means that the organizational climate variable significantly influences journalists' work motivation, or the first hypothesis is accepted. The significant influence of compensation on work motivation is demonstrated by the calculated t-value of 7.301 and the t-table value of 1.976. A significance level of 0.000 is lower than the alpha value of 0.025. This indicates that compensation significantly influences employee work motivation. The first hypothesis is accepted, and there is a significant positive influence between organizational climate and compensation on work motivation, as seen from the coefficient of determination (R²) of 0.630 with p = 0.000 < 0.050, indicating a 63.0% contribution of organizational climate and compensation to work motivation. These results are supported by the F-test, where the calculated F-value is greater than the F-table value, which is 992.749, and the F-table value is 3.06, with a significance level of 0.000 < 0.050.